Enhancing learning performance through knowledge management - Momaya, K. (2005)
Importance of learning is increasing as individuals, teams and organizations face unprecedented challenges of acquiring new skills in face of turbulent times. At the same time many organizations have felt the need for leveraging their knowledge-based assets through formal programmes of knowledge management (KM). Technology can play a very important enabling role in both the above important inter-linked issues: learning and K.M. This paper aims to evolve debate and achieve greater understanding of the subjects matter and potential synergies. The learning presented herein is based on factual experiments undertaken by the author and supporting team on a number of pilot projects, real life situations and research/consulting projects during the past four years. The focus is on the role of technology to enable design better systems as one moves towards E-learning paradigm in a digital era. Different experiments conducted are portrayed in 'caselets' forms to offer better feel for realities and relate learning with context. Learning and action opportunities are given so that aspiring managers and scientists can develop their own experiments. -Reproduced.
Keywords: Learning; Knowledge management